Personalized Medicines in Pharmaceutics: Drug Delivery System - R.Shireesh Kiran; Jaggayagari Sarika; Panuganti Pranavi; Kondam Rithikesh; T. Rama Rao (Emerging Trends in Personalized Medicines, 2024)
Pharmaceutics personalized medicine is a developing area that seeks to customize medical interventions for specific patients. Instead of a one-size-fits-all approach, personalized medicine focuses on developing treatments that consider a person’s unique characteristics, such as their genetic makeup, environment, and lifestyle. This allows for more effective treatment outcomes, as drugs are specifically designed to work best for each patient, reducing side effects and improving therapeutic results. In pharmaceutics, this involves creating customized drug formulations, dosages, and delivery methods that cater to the needs of specific patients. Advances in technologies like genomics, proteomics, and bioinformatics, along with digital health platforms that monitor patient data in real-time, are helping to speed up the progress of personalized medicine. These innovations are changing how drugs are discovered, tested, and administered in clinical settings, leading to more accurate and efficient healthcare solutions. However, there are still challenges to overcome, such as the high cost of developing personalized treatments, complex regulations, and managing large amounts of patient data. It offers the opportunity to create more effective, safer, and patient- specific treatments that can transform the way diseases are treated.
Keywords: Bioinformatics; Customized Treatment; Digital Health Platforms; Personalized medicine; healthcare innovation